MOLECULAR GENETIC PROFILE OF KAZAKHSTAN POPULATIONS OF CATTLE BREEDS - Shamshidin Alzhan Smailuly; Kharzhau Ainur; Baimukanov Dastanbek Asylbekovich; Sermyagin Aleksandr Aleksandrovich (Scientific Journal of Pedagogy and Economics, 2019)
Modern methods of cattle breeding provide for active use of new breeding programs. The introduction of molecular-genetic studies predetermines the prospects for the use of DNA microsatellites (STR-loci). These microsatellites are widely used for studying the allele pool of farm animals. Based on the above-mentioned, the aim of the research was to study the genetic structure and analysis of the degree of genetic differentiation of cattle breeds in the Republic of Kazakhstan, based on molecular genetic information.As a biological material for research, the semen of bulls was used. The paper presents research materials of DNA profiles on 11 microsatellite loci of dairy (Holstein, Black-and-white, Aulie-Ata), combined (Alatau) and meat (Auliekol, Kazakh whiteheaded) breeds. The microsatellite profile of animals was represented by the following loci: BM1824, ETH225, INRA23, BM2113, SPS115, ETH10, TGLA122, TGLA126, TGLA227, ETH3, TGLA53, included in the recommended panel ICAR and ISAG. The genetic pattern of populations was analyzed according to F-statistics. Genetic identity indicators were calculated according to Nei. Populations’ heterozygosity was determined according to the Wright’s fixation index. The differences in breeds in the direction of productivity were analyzed by the share of variations of microsatellite loci. As a result of research, it was found that the implementation of molecular genetic methods in the selection of farm animals will significantly increase the development potential of cattle breeding resources available in the Republic of Kazakhstan.